C5a Regulates IL-1β Production and Leukocyte Recruitment in a Murine Model of Monosodium Urate Crystal-Induced Peritonitis - Khameneh, Hanif J.; Ho, Adrian W. S.; Laudisi, Federica; Derks, Heidi; Kandasamy, Matheswaran; Sivasankar, Baalasubramanian; Teng, Gim Gee; Mortellaro, Alessandra (Frontiers in Pharmacology, 2017)
Gouty arthritis results from the generation of monosodium urate (MSU) crystals within joints. These MSU crystals elicit acute inflammation characterized by massive infiltration of neutrophils and monocytes that are mobilized by the pro-inflammatory cytokine IL-1β. MSU crystals also activate the complement system, which regulates the inflammatory response; however it is unclear whether or how MSU-mediated complement activation is linked to IL-1β release in vivo, and the various roles that might be played by individual components of the complement cascade. Here we show that exposure to MSU crystals in vivo triggers the complement cascade, leading to the generation of the biologically-active complement proteins C3a and C5a. C5a, but not C3a, potentiated IL-1β and IL-1α release from LPS–primed MSU-exposed peritoneal macrophages and human monocytic cells in vitro; while in vivo MSU–induced C5a mediated murine neutrophil recruitment as well as IL-1β production at the site of inflammation. These effects were significantly ameliorated by treatment of mice with a C5a receptor antagonist. Mechanistic studies revealed that C5a most likely increased NLRP3 inflammasome activation via production of reactive oxygen species (ROS), and not through increased transcription of inflammasome components. Therefore we conclude that C5a generated upon MSU-induced complement activation increases neutrophil recruitment in vivo by promoting IL-1 production via the generation of ROS, which activate the NLRP3 inflammasome. Identification of the C5a receptor as a key determinant of IL-1-mediated recruitment of inflammatory cells provides a novel potential target for therapeutic intervention to mitigate gouty arthritis.